Influence of In content in InGaN barriers on crystalline quality and carrier transport of GaN-based light-emitting diodes. (17th February 2016) - Lin, Zhiting; Wang, Haiyan; Lin, Yunhao; Yang, Meijuan; Wang, Wenliang; Li, Guoqiang
Abstract: The influence of In content in InGaN barriers on the crystalline quality and carrier transport of GaN-based light-emitting diodes (LEDs) is studied by numerical and experimental investigations. The optimal In content of InGaN barriers is hence obtained. It is found that carrier concentration and crystalline quality degradation are a pair of opposite influential factors as In content increases. In content of 1.2% is optimal because it is the balance value at which a huge gain of carrier concentration is achieved without crystalline degradation. In content of 1.2% in InGaN barriers leads to a remarkable enhancement in both the light output power and external quantum efficiency (EQE) of LEDs. In such cases, the LED's light output power and the EQE increase by 15.4% and 10.3% at a current of 70 mA, respectively. This work demonstrates the possibility of achieving high-performance LEDs with an aggravated efficiency droop, and is of great interest for the commercial development of GaN-based LEDs.